PELATIHAN TATA KELOLA KEUANGAN PRODUK KELAPA KOPRA PADA KELOMPOK UMKM DESA LAPEO KECAMATAN CAMPALAGIAN KABUPATEN POLEWALI MANDAR - Ariyandani, Nur; Rahmayanti Rivai, Dian; Fitriani, Nur (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2023)
Lapeo village is an area with a quite large produce of agricultural, especially copra coconut farmers. It is usually used as a raw material for making VCO (virgini coconut oil). One of the SMEs in Lapeo village carries out these businesses. However, the SMEs have a problem in financial process. Precisely, they do not know how much income they earn, expenses, and capital they spend. Therefore, the aim of this service is to provide training regards to financial management to the copra coconut SMEs. The method to implementing this activity is carried out through 3 steps, firstly, direct inspection, secondly, analyzing problems, and thirdly, carrying out financial training. The results are the SMEs expected to be able to carry out routine financial records and separate personal and business financial records. Furthermore, this training received a positive responsesfrom the participants.